Circulating levels of sulphasalazine and its metabolites and their relation to the clinical efficacy of the drug in ulcerative colitis. Issue 8 (August 1980) - Azad Khan, A K; Truelove, S C
Abstract : One hundred and eighty-five patients with ulcerative colitis have been studied serially while receiving regular maintenance treatment with sulphasalazine (SASP) in a dose of 0.5 g four times daily. The circulating levels of the drug and its principal metabolites during remission do not influence the liability to relapse. When relapse does occur, the circulating level of sulphapyridine falls and remains depressed until remission occurs. This fall during a relapse is most pronounced when the patient suffers from universal colitis and is least marked in cases of distal colitis.